REANALYSIS SIFAT MEKANIS MATERIAL KOMPONEN ALAT ANGKAT KENDARAAN NIAGA KAPASITAS 2 TON - Reki Walewangko; Rudy Poeng; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
Design need the strength of material information. One information on the mechanical properties of the components is the tensile strength. Results of tensile tests are stress, strain and curveof the material. The construction of a lifting device for commercial vehicle with a capacity of 2 tonnes by students of Mechanical Engineering University of Sam Ratulangi (Unsrat) using allowable strength from specifications of the material. Reanalysis of the material used in the design results tensile strength 57. 081 N/mm2 , were classified as material stress state Fe 490 grade III to limit the allowable tensile stress of 40 to 60 (N/mm2), thereby verifying the basicÂ  information of the design. Keywords: Lifting Equipment Components, Tensile Strength Test.